Characterization and in vitro assembly of tick-borne encephalitis virus C protein - Kaufman, Filip; Dostálková, Alžběta; Pekárek, Lukáš; Thanh, Tung Dinh; Kapisheva, Marina; Hadravová, Romana; Bednárová, Lucie; Novotný, Radim; Křížová, Ivana; Černý, Jiří; Grubhoffer, Libor; Ruml, Tomáš; et al. (FEBS letters, 2020)
Tick-borne encephalitis virus (TBEV), a member of flaviviruses, represents a serious health threat by causing human encephalitis mainly in central and eastern Europe, Russia, and northeastern Asia. As no specific therapy is available, there is an urgent need to understand all steps of the TBEV replication cycle at the molecular level. One of the critical events is the packaging of flaviviral genomic RNA by TBEV C protein to form a nucleocapsid. We purified recombinant TBEV C protein and used a combination of physical-chemical approaches, such as size-exclusion chromatography, circular dichroism, NMR spectroscopies, and transmission electron microscopy, to analyze its structural stability and its ability to dimerize/oligomerize. We compared the ability of TBEV C protein to assemble in vitro into a nucleocapsid-like structure with that of dengue C protein.
Keywords: viry klíšťové encefalitidy; virus dengue; nukleokapsida; Magnetic Resonance Spectroscopy; gelová chromatografie; virové proteiny; Dengue Virus; Viral Proteins; cirkulární dichroismus; Chromatography, Gel; magnetická rezonanční spektroskopie; Encephalitis Viruses, Tick-Borne; Nucleocapsid; Recombinant Proteins; Circular Dichroism; koncentrace vodíkových iontů; Hydrogen-Ion Concentration; rekombinantní proteiny